Prediction of maneuvering coefficients of Delft catamaran 372 hull form - Duman, S.; Bal, S. (CRC PRESS-BALKEMA, 2020)
Many studies have been carried out so far in order to determine the maneuvering characteristics of mono-hull surface ships. Studies on multi-hull vessels, on the other hand, are rarely found in literature and most of them have focused on the resistance characteristics of such vessels. In this study, it is aimed to calculate the hydrodynamic maneuvering coefficients of a high-speed catamaran by utilizing the CFD (Computational Fluid Dynamics) method. Delft Catamaran 372 hull form has been chosen. Computerized PMM (Planar Motion Mechanism) is conducted for the selected cases using overset grid technique. The turbulent viscous flow around the catamaran hull is solved by a commercial unsteady RANS solver software based on FVM (Finite Volume Method) including the free surface effects. The computational domain is divided into two main fields; the static grid and the dynamic overset grid, and is discretized with hexahedral elements. The feasibility and competence of the CFD method in predicting maneuvering coefficients of the catamaran hull form are discussed.
Keywords: PERFORMANCE; Science & Technology - Other Topics; Engineering